2017
DOI: 10.1051/0004-6361/201629186
|View full text |Cite
|
Sign up to set email alerts
|

Internal rotation of 13 low-mass low-luminosity red giants in theKeplerfield

Abstract: Context. The Kepler space telescope has provided time series of red giants of such unprecedented quality that a detailed asteroseismic analysis becomes possible. For a limited set of about a dozen red giants, the observed oscillation frequencies obtained by peak-bagging together with the most recent pulsation codes allowed us to reliably determine the core/envelope rotation ratio. The results so far show that the current models are unable to reproduce the rotation ratios, predicting higher values than what is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
65
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 45 publications
4
65
0
Order By: Relevance
“…The case of KIC 3955033 is illustrative, with a negative surface rotation when using ζ; the use of ζ m provides a null value (5±20 nHz). This case also confirms the general situation shown by previous works (Goupil et al 2013;Di Mauro et al 2016;Triana et al 2017): deriving surface rotation can be achieved for the low RGB only.…”
Section: Surface Rotationsupporting
confidence: 91%
See 1 more Smart Citation
“…The case of KIC 3955033 is illustrative, with a negative surface rotation when using ζ; the use of ζ m provides a null value (5±20 nHz). This case also confirms the general situation shown by previous works (Goupil et al 2013;Di Mauro et al 2016;Triana et al 2017): deriving surface rotation can be achieved for the low RGB only.…”
Section: Surface Rotationsupporting
confidence: 91%
“…As shown by subsequent works (e.g., Deheuvels et al 2014;Di Mauro et al 2016;Triana et al 2017), it is difficult to derive from the observed rotational splittings more than these two mean quantities. Again, we have to solve the ambiguity of the meaning of ζ in Eq.…”
Section: Rotational Splittingmentioning
confidence: 96%
“…For KIC 9163796 we have, however, an estimate for the surface rotation rate from the dominant period of the light curve modulation ( f 1 = 87±8 nHz). The core-surface rotation gradient is typical for RGB stars (Ω core /Ω envelope ≃ 6 to 30 times, Beck et al 2012Beck et al , 2014Deheuvels et al 2012Deheuvels et al , 2014Di Mauro et al 2016;Goupil et al 2013;Triana et al 2017) but appears a the lower end of the values found so far. Yet we note that this is small number statistics.…”
Section: Core Rotation and Surface Rotationmentioning
confidence: 54%
“…Internal rotation rates as a function of depth have been estimated for a number of red giants using a forward modelling approach (Beck et al 2014(Beck et al , 2018 or by means of rotational inversions (Deheuvels et al 2012(Deheuvels et al , 2014Di Mauro et al 2016Triana et al 2017). However, the exact shape of the internal rotation profile remains unknown, as only core and surface rotation rates can currently be measured.…”
Section: Introductionmentioning
confidence: 99%